1990
DOI: 10.1007/bf02003234
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bacterial endotoxin on plasma concentration of haptoglobin and fibrinogen in rats treated with metopyrone

Abstract: During the acute phase of the inflammatory process there is a characteristic increase in some plasma proteins called collectively acute phase reactants (APR) as well as in the levels of corticosteroids. A bacterial endotoxin (LPS) that induces a strong acute phase response, indicated by high levels of fibrinogen and haptoglobin, did not show this effect when administered to rats treated previously with metopyrone, a specific inhibitor of corticosteroid hormone synthesis. These results suggest that adequate lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…There is some evidence to suggest that the cytokine acute-phase response may be mediated through the increased release of glucocorticoid hormones (Dinarello, 1984). In both in vivo and in vitro studies with rats, it has been shown that glucocorticoids, rather than being directly stimulatory, are permissive for the hepatic production of acute-phase reactants (Gauldie, 1989;Silveira and Limaos, 1990). Further, it has been shown that IL-1 is capable of both modulating and interacting with glucocorticoids (Gauldie, 1989).…”
Section: Discussionmentioning
confidence: 96%
“…There is some evidence to suggest that the cytokine acute-phase response may be mediated through the increased release of glucocorticoid hormones (Dinarello, 1984). In both in vivo and in vitro studies with rats, it has been shown that glucocorticoids, rather than being directly stimulatory, are permissive for the hepatic production of acute-phase reactants (Gauldie, 1989;Silveira and Limaos, 1990). Further, it has been shown that IL-1 is capable of both modulating and interacting with glucocorticoids (Gauldie, 1989).…”
Section: Discussionmentioning
confidence: 96%
“…Lewis et al (1989) reported an increase in plasma fibrinogen from 1.0-1.7 mg/mL (normal) to 4.3-5.2 mg/mL in a rat model of adjuvant-induced inflammation. A twofold increment in plasma fibrinogen was reported in rats intraperitoneally injected with lipopolysaccharide (Silveira and Limoas, 1990).…”
Section: Fibrinogenmentioning
confidence: 96%